The Appeal of Modern Retail: Evaluation of Location, Price, and Product Diversity as a Determinant of Consumer Satisfaction - Rifky Fauzi; Ryan Kurniawan (Journal of Islamic Economics and Business, 2024)
This study aims to analyze the effect of location, price, and product diversity on customer satisfaction at Alfamart in Bandung Regency. The background of this research is based on the rapid development of modern retail and the importance of marketing factors in maintaining customer satisfaction. Strategic location, competitive pricing, and the provision of diverse products are believed to be important elements in attracting and retaining customers. The research method used is quantitative with a descriptive approach. Data were collected through distributing questionnaires to 210 Alfamart consumer respondents, then analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) Version 3.2.9 method. The results showed that partially and simultaneously, the variables of location, price, and product diversity had a significant effect on customer satisfaction. This finding indicates that the more strategic the location of the store, the more affordable the price, and the more diverse the products offered, the higher the level of customer satisfaction. The practical implication of this research is the need for a marketing strategy that focuses on improving store accessibility, adjusting prices to consumer purchasing power, and diversifying products in accordance with local market needs.